Repurposing the McoTI-II rigid molecular scaffold in to inhibitor of `papain superfamily' cysteine proteases - Mishra, Manasi; Singh, Vigyasa; Tellis, Meenakshi B.; Joshi, Rakesh S.; Singh, Shailja (Pharmaceuticals, 2021)
Clan C1A or `papain superfamily' cysteine proteases are key players in many important physiological processes and diseases in most living systems. Novel approaches towards the development of their inhibitors can open new avenues in translational medicine. Here, we report a novel design of a re-engineered chimera inhibitor Mco-cysteine protease inhibitor (CPI) to inhibit the activity of C1A cysteine proteases. This was accomplished by grafting the cystatin first hairpin loop conserved motif (QVVAG) onto loop 1 of the ultrastable cyclic peptide scaffold McoTI-II. The recombinantly expressed Mco-CPI protein was able to bind with micromolar affinity to papain and showed remarkable thermostability owing to the formation of multi-disulphide bonds. Using an in silico approach based on homology modelling, protein-protein docking, the calculation of the free-energy of binding, the mechanism of inhibition of Mco-CPI against representative C1A cysteine proteases (papain and cathepsin L) was validated. Furthermore, molecular dynamics simulation of the Mco-CPI-papain complex validated the interaction as stable. To conclude, in this McoTI-II analogue, the specificity had been successfully redirected towards C1A cysteine proteases while retaining the moderate affinity. The outcomes of this study pave the way for further modifications of the Mco-CPI design for realizing its full potential in therapeutics. This study also demonstrates the relevance of ultrastable peptide-based scaffolds for the development of novel inhibitors via grafting.
Keywords: Cathepsin; Clan CA cysteine proteases; cyclotide; cystatin; McoTI-II; papain; protein engineering

Cyclic peptide engineered from phytocystatin inhibitory hairpin loop as an effective modulator of falcipains and potent antimalarial - Mishra, Manasi; Singh, Vigyasa; Tellis, Meenakshi B.; Joshi, Rakesh S.; Pandey, Kailash C.; Singh, Shailja (Journal of Biomolecular Structure & Dynamics, 2022)
Cystatins are classical competitive inhibitors of C1 family cysteine proteases (papain family). Phytocystatin superfamily shares high sequence homology and typical tertiary structure with conserved glutamine-valine-glycine (Q-X-V-X-G) loop blocking the active site of C1 proteases. Here, we develop a cysteine-bounded cyclic peptide (CYS-cIHL) and linear peptide (CYS-IHL), using the conserved inhibitory hairpin loop amino acid sequence. Using an in silico approach based on modeling, protein-peptide docking, molecular dynamics simulations and calculation of free energy of binding, we designed and validated inhibitory peptides against falcipain-2 (FP-2) and -3 (FP-3), cysteine proteases from the malarial parasite Plasmodium falciparum. Falcipains are critical hemoglobinases of P. falciparum that are validated targets for the development of antimalarial therapies. CYS-cIHL was able to bind with micromolar affinity to FP-2 and modulate its binding with its substrate, hemoglobin in in vitro and in vivo assays. CYS-cIHL could effectively block parasite growth and displayed antimalarial activity in culture assays with no cytotoxicity towards human cells. These results indicated that cyclization can substantially increase the peptide affinity to the target. Furthermore, this can be applied as an effective strategy for engineering peptide inhibitory potency against proteases.
Keywords: Cyclic peptide; falcipain inhibitors; falciparum; P; Phytocystatin; protein interaction mimics; protein&#8211